Superovulation, in vivo Embryo Recovery and Cryopreservation for Aoudad (Ammotragus Lervia) Females Using Osmotic Pumps and Vitrification: A Preliminary Experience and its Implications for Conservation. (March 2013) - López-Saucedo, Janet; Ramón-Ugalde, Julio Porfirio; de Barroso-Padilla, José Jesús; Gutiérrez-Gutiérrez, Antonio Martin; Fierro, Reyna; Piña-Aguilar, Raul Eduardo
The aoudad (Ammotragus lervia) is a wild ruminant considered the living ancestor of domestic sheep and goats. The original distribution of aoudads includes several countries in the North of Africa, but it has been introduced, for trophy-hunting purposes, into other countries (USA, Mexico and Spain). The species was declared vulnerable in the 2012 IUCN's Red List and is also included in the CITES II Appendix. Surprisingly, little is known about its conservation status or the reproductive biology of the natural populations. There are some reports of the application of basic assisted-reproduction techniques in captive aoudads. In this preliminary study, we explored the feasibility of implementing assisted reproduction procedures in captive aoudad females using non-traditional techniques for in vivo embryo production. This approach was used to obtain the best results using the minimum possible number of animals. Three aoudad females were synchronized using a domestic sheep protocol and subcutaneous osmotic pumps for the delivery of follicle-stimulating hormone. A mini-surgical approach combined with laparoscopy was performed to obtain in vivo -produced embryos. All females had an ovulatory response of more than three corporea lutea, but only five good quality morulae were obtained from one female. Those were cryopreserved by vitrification using a Cryotop®. In conclusion, our approach was successful in obtaining in vivo embryos using a limited number of females. Further studies are necessary to optimize the fertilization rate and clarify the effect of our protocol on embryo implantation and the production of offspring.